Middle meningeal artery arising from the basilar artery: report of a case and its probable embryological mechanism. (19th April 2011) - Kumar, Subhash; Mishra, Nalin K
Abstract : An extremely rare variation of the (left) middle meningeal artery (MMA) originating from the basilar artery, detected incidentally during cerebral angiography, is reported. The right MMA was normal and an accessory meningeal artery arising from the maxillary artery was present on both the sides. The foramen spinosum on the variant side was absent. This abnormal origin of the MMA can be explained by the presence of a perineural arterial network in the region of the Gasserian ganglion, formed by branches of the developing basilar and stapedial arterial systems; the middle meningeal–basilar arterial channel opening up in the absence of a normally developing MMA.